Chimeras of P4-ATPase and Guanylate Cyclase in Pathogenic Protists. Issue 4 (April 2020) - Günay-Esiyok, Özlem; Gupta, Nishith
Abstract : Apicomplexan parasites harbor chimeric proteins embodying P4-type ATPase and guanylate cyclase domains. Such proteins – serving as the actuator of cGMP signaling in this group of important pathogens – are indeed unusual in terms of their sheer size, modus operandi, and evolutionary repurposing. Much like the mythological Sphinx, a human-lion chimeric creature that posed challenging riddles, the P4-type ATPase–guanylate cyclase chimeras present both structural and functional conundrums. Here we review the function, topology, mechanism, and intramolecular coordination of the alveolate-specific chimeras in apicomplexan parasites. The steep technological challenge to understand these molecular Sphinxes will surely keep many interdisciplinary researchers busy in the next decades. Highlights: Infection, pathogenesis, and transmission of apicomplexan parasites, such as Toxoplasma and Plasmodium spp., depend on cGMP-mediated regulation of subcellular events. Apicomplexans have evolved exclusive proteins containing P4-type ATPase and guanylate cyclase domains, involved in phospholipid flipping and cGMP synthesis, respectively. The ATPasep –GC chimeras are essential for the life cycle of Toxoplasma and Plasmodium, where they govern gliding motility, invasion, and egress. Understanding functional evolution of the CDC50–ATPasep –GC–UGO complex in apicomplexans may reveal parasite-specific repurposing and coupling of cGMP signaling and lipid flipping. The structure and mechanism of human and yeast P4-ATPases provide promising clues to unravel the functioning of ATPasep –GC chimeras in alveolates.